2021
DOI: 10.1186/s13287-021-02296-8
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from umbilical cord mesenchymal stromal cells alleviate pulmonary fibrosis by means of transforming growth factor-β signaling inhibition

Abstract: Background Pulmonary fibrosis (PF), the end point of interstitial lung diseases, is characterized by myofibroblast over differentiation and excessive extracellular matrix accumulation, leading to progressive organ dysfunction and usually a terminal outcome. Studies have shown that umbilical cord-derived mesenchymal stromal cells (uMSCs) could alleviate PF; however, the underlying mechanism remains to be elucidated. Methods The therapeutic effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…In fact, the clinical transition to MSC-EVs is still in its infancy and needs to face many challenges. Here, we summarize the studies of MSC-EVs administration in pulmonary fibrosis in vivo in Table 2 [ 20 , 108 , 117 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ] and an overview of therapeutic modalities of MSC-EVs for IPF in Figure 3 .…”
Section: Msc-evs Treatment Administration For Ipfmentioning
confidence: 99%
“…In fact, the clinical transition to MSC-EVs is still in its infancy and needs to face many challenges. Here, we summarize the studies of MSC-EVs administration in pulmonary fibrosis in vivo in Table 2 [ 20 , 108 , 117 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ] and an overview of therapeutic modalities of MSC-EVs for IPF in Figure 3 .…”
Section: Msc-evs Treatment Administration For Ipfmentioning
confidence: 99%
“…They demonstrated that human UC-MSC-derived EVs alleviate pulmonary fibrosis by repressing the TGF-β signaling pathway. Mechanistically, miR-21 and miR-23 in the EVs play crucial elements that contribute to anti-myofibroblast differentiation by downregulating TGF-β2 and TGF-βR2 expression [ 53 ]. While studies on MSC-derived EVs have dramatically increased, the development of clinical medicines is still in its infancy.…”
Section: Extracellular Vesicle-based Therapy For Idiopathic Pulmonary...mentioning
confidence: 99%
“…Since stem cell-derived EVs naturally contain various bioactive molecules derived from stem cells, the EV-based therapeutics have several advantages in clinical therapies. Currently, various types of cell-derived EVs have been studied in experimental pulmonary fibrosis models, such as MSCs [50][51][52][53][54], adult stem cells [55], fibroblasts [56,57], bronchial epithelial cells [10], and lung tissue spheroid cells [11] (Table 2).…”
Section: Extracellular Vesicle-based Therapy For Idiopathic Pulmonary...mentioning
confidence: 99%
“…However, exosomal miR-23a inhibited myofibroblast differentiation through inhibition of the TGF-β/SMAD pathway during wound healing ( Fang et al, 2016 ), and was thus used in the experimental treatment of PF ( Tan et al, 2018 ). Moreover, extracellular vesicles derived from umbilical cord MSCs enriched with miR-23 alleviated PF by inhibition of TGF-β signaling ( Shi et al, 2021 ). The precise effect and mechanism of the miR-23 family requires further investigation ( Table 10 ).…”
Section: Potential Mirna Targets For Pulmonary Fibrosismentioning
confidence: 99%